Soil Fertility - Nuhu Issaka, Roland (IntechOpen, 2012)
Soil Fertility book presents nine chapters written by renowned soil fertility experts from Africa, Asia and South America. The book is divided into two sections. Section 1, Biological Processes and Integration of Inorganic and Organic Fertilizers for Soil Fertility Improvement, examines biological processes that can enhance the soil fertility. It discusses the use of both organic and inorganic fertilizers and their integration in improving soil fertility. The second section, Improving Fertilizer Recommendation and Efficiency, looks at the state-of-the-art in leaf sampling and analysis. Proper leaf sampling and standardized methods of analysis are important steps in providing good recommendations.